Semantics of building (verb) and building (does) in systems (Journal of the College of Basic Education, 2023)
(verb) and (does) are among the verb structures in Arabic, and the verb is an important pillar in constructing verbs.The sentence because it is the predicate and it is the center of the comment in the actual sentence, and the verb has received attentionThe ancient grammarians (1) However, the study of the verb for some grammarians was oriented towards workAnd the worker and the done. The verb is a strong factor that has certain characteristics in the work. As for the connotationsThey limited themselves to two meanings only in their definition of it, namely: the meaning of the event and the meaning of time.The verb is what indicates an event associated with a time, and they called the construction (verb) the name (verbthe past) and the past tense is, in fact, only one sign among manyThis structure presents it in the systems, and they called the structure (does) the name (present tense) and theseThe noun has nothing to do with any of the semantics of the construction (does), but it is called a present tenseTo match names, that is, to be similar to them in parsing.“And according to this, modern textbooks follow in defining the verb.” (2) It seems that the reasonIn defining the verb when defining in terms of (event and time) only, the grammarians studiedThe verb is isolated, i.e. outside the systems or outside the context in which it is, and the verb does not appear withoutThese two signs (event and one time direction) are outside the systems, but when we notice the verbWithin the systems or within the context in which it was mentioned, other important indications and trends emerge.I will mention them in what follows with quoting verses from the Holy Qur’an to clarify the implications.provided by the builder in the systems.